2022
DOI: 10.1002/jcu.23311
|View full text |Cite
|
Sign up to set email alerts
|

Atrial thrombosis: Not only left, think also about right!

Abstract: Atrial fibrillation (AF) is the most common arrhythmia in the general population. Systemic thromboembolism from left atrial appendage (LAA) thrombosis is a well‐known complication of AF, whereas thromboembolic complications from a right atrial (RA) thrombus are infrequent. Nevertheless, the prevalence of RA thrombosis is debated; despite having a low prevalence in echocardiographic studies, the higher prevalence found in autoptic studies rises the hypothesis of an under detection of RA clots, possibly related … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…A possible explanation is that vascular dysfunction and platelet activation also occurred in other sites, and the mean CHA 2 DS 2 -VASc scores were 2.5 ± 1.6 in this study, which means most patients had higher thromboembolism risk than previous studies. In a pile of papers, it was demonstrated that thrombi were not rare in the right atrium [18,19,20] .Hence sP-selectin and vWF levels in peripheral vessels maybe more accurate and comprehensive, instead of those in left atrium blood.…”
Section: Discussionmentioning
confidence: 99%
“…A possible explanation is that vascular dysfunction and platelet activation also occurred in other sites, and the mean CHA 2 DS 2 -VASc scores were 2.5 ± 1.6 in this study, which means most patients had higher thromboembolism risk than previous studies. In a pile of papers, it was demonstrated that thrombi were not rare in the right atrium [18,19,20] .Hence sP-selectin and vWF levels in peripheral vessels maybe more accurate and comprehensive, instead of those in left atrium blood.…”
Section: Discussionmentioning
confidence: 99%
“…This critical scenario gives rise to mechanical impediment, and in its most dire manifestation, precipitates sudden cardiac fatality; (2) secondly, an equally formidable facet of this risk profile resides in the propensity of the thrombus to dislodge. Such an eventuality poses an immediate and hazardous threat, as the liberated thrombus embarks on a treacherous journey through the pulmonary circulation, culminating in a catastrophic and potentially fatal event—a massive pulmonary embolism 10 . Hence, prompt diagnosis and intervention assume paramount importance in such cases.…”
Section: Discussionmentioning
confidence: 99%
“…Such an eventuality poses an immediate and hazardous threat, as the liberated thrombus embarks on a treacherous journey through the pulmonary circulation, culminating in a catastrophic and potentially fatal event-a massive pulmonary embolism. 10 Hence, prompt diagnosis and intervention assume paramount importance in such cases.…”
Section: Introductionmentioning
confidence: 99%
“…11 Subramaniam et al 17 suggest that AF is associated with reduced right and left atrial attachments and ejection velocity, and thus the greater width of right atrial attachments and inadequate anatomical remodeling in some patients may explain the association of this group of patients with AF and their right atrial attachment thrombus. Also, Degiovanni et al 18 concluded that a differential diagnosis of thrombus and other intracardiac masses (most commonly atrial mucinous tumors) is needed when faced with a right atrial mass. We need to be alert to the possibility of atrial thrombosis if the patient has a history of prior cardiac surgery and AF or other underlying medical conditions.…”
Section: Discussionmentioning
confidence: 99%